Association between serum vitamin D status and the anti-seizure treatment in Chinese children with epilepsy - Dong, Na; Guo, Hong-Li; Hu, Ya-Hui; Yang, Jiao; Xu, Min; Ding, Le; Qiu, Jin-Chun; Jiang, Zhen-Zhou; Chen, Feng; Lu, Xiao-Peng; Li, Xiao-Nan (Frontiers in Nutrition, 2022)
Objective: To compare the serum 25-OH-VitD (the major marker of VitD status) levels between healthy children and children with epilepsy before initiation of and during ASMs treatment and to evaluate the potential influence factors on 25-OH-VitD levels. Another major aim was to assess the potential role of VitD supplementation. Methods: For comparison, we retrospectively collected data from 6338 healthy children presenting to Health Care Department and 648 children visiting primary care pediatricians with symptoms of epilepsy in Children’s Hospital of Nanjing Medical University from January 2019 to June 2021. The demographic and biochemical characteristics of each child were extracted from the hospital internal system. Results: Serum 25-OH-VitD levels in 648 children with epilepsy were significantly lower than those of 6338 healthy children (P < 0.0001), and the percentage of VitD insufficiency and deficiency status in pediatric patients was 49.19%. Of note, the serum 25-OH-VitD levels in children with newly-diagnosed epilepsy before receiving any ASMs treatment were also significantly lower than those healthy subjects. Interestingly, ASMs therapy, alone or in combination, did not consistently reduce baseline serum VitD levels in children with epilepsy. The lower serum VitD level in children with epilepsy than in healthy children might be related to the epilepsy itself, rather than the ASMs treatment. As expected, VitD supplementation substantially increased the serum 25-OH-VitD levels (P < 0.0001). More critically, children with epilepsy receiving VitD supplementation achieved good seizure control in our study. Significance: In this study, the childhood epilepsy before initiation of and during ASMs treatment decreased the serum 25-OH-VitD concentrations, suggesting a clear association between epileptic disease and the risk of VitD deficiency. ASMs coadministration and long-term valproic acid treatment did not worse VitD-deficiency status, but in the small group receiving VitD there was a significant improvement in reduction of seizure frequency. Therefore, pediatric clinicians are urged to raise public awareness of epilepsy-associated VitD deficiency.